Analysis of the Utilization of Learning Devices in Social Studies towards HOTS - Sutaryanto Sutaryanto (Universitas Pendidikan Indonesia (UPI), 2020)
Higher Order Thinking Skill (HOTS) learning is needed to support the implementation of learning in the 2013 curriculum. Learning will be carried out well if it is accompanied by a good learning plan, which is required learning tools that support the training of HOTS students. The purpose of this study was to determine how to analyze the application of learning tools to HOTS students of SD Negeri 9 Purwodadi, especially in social studies learning. The approach in this research uses a qualitative research approach with descriptive research methods. The data collection techniques used in this research were observation, interview and documentation. The instruments used in this study were observation sheets of learning activities carried out by the teacher, documentation of learning tools used by teachers and students during learning activities and interview sheets with open answers. The results showed that learning that can support higher order thinking or Higher Order Thinking Skills (HOTS) requires indicators on the aspects of analyzing, evaluating and creating. Social studies learning at SD Negeri 9 Purwodadi has not applied the HOTS learning concept. Learning tools in the form of syllabus, lesson plans and teaching materials at SD Negeri 9 Purwodadi, especially in social studies learning, still use conventional learning tools. The scoring system only emphasizes the cognitive aspects. Learning is still teacher-centered. The results showed that learning that can support higher order thinking or Higher Order Thinking Skills (HOTS) requires indicators on the aspects of analyzing, evaluating and creating. Social studies learning at SD Negeri 9 Purwodadi has not applied the HOTS learning concept. Learning tools in the form of syllabus, lesson plans and teaching materials at SD Negeri 9 Purwodadi, especially in social studies learning, still use conventional learning tools. The scoring system only emphasizes the cognitive aspects. Learning is still teacher-centered. The results showed that learning that can support higher order thinking or Higher Order Thinking Skills (HOTS) requires indicators on the aspects of analyzing, evaluating and creating. Social studies learning at SD Negeri 9 Purwodadi has not applied the HOTS learning concept. Learning tools in the form of syllabus, lesson plans and teaching materials at SD Negeri 9 Purwodadi, especially in social studies learning, still use conventional learning tools. The scoring system only emphasizes the cognitive aspects. Learning is still teacher-centered. The scoring system only emphasizes the cognitive aspects. Learning is still teacher-centered. The scoring system only emphasizes the cognitive aspects. Learning is still teacher-centered.